(untitled) (Contemporary Journal of Social Science Review, 2025)
1857 is the turning point in our history which not only dealt a severe blow to Muslims politically and economically, but also made them suffer from conflict and hesitation in terms of mental, intellectual and cultural aspects. It has become clear that this war was not limited to the extent of rebellion but was all over North and Central India. The reason for its failure is to start suddenly without organization and proper preparation. The workers of this war lacked mutual cooperation but also lacked combat skills. Besides, at the same time, some elements of other countries also opposed instead of supporting and stood in support of the British government. It is also worth noting that both Muslims and Hindus participated in the war of independence, but after its failure, the punishment fell to the Muslims. There are several reasons for this special treatment of Muslims by the British. The way Islamic teachings and beliefs have been distorted and presented in Europe has created feelings of hatred and contempt against Muslims in Western minds. The mistrust that had arisen from the time of the Crusades towards the Muslims did not diminish even after the passage of centuries. Apart from this, the special reason is that the power of the Muslims was taken away by the British for centuries. Therefore, the resentment of the Muslims towards the British was more than that of the Hindus and the British were aware of this. The British also saw in the war that the Muslims were less in number than the Hindus and their number in the army was small, but still they fought with more zeal. The British were also aware that Muslim scholars had been inciting Muslims for Jihad even before 1857.